Immunostimulation by OX40 Ligand Transgenic Ewing Sarcoma Cells - Reuter, Dajana; Staege, Martin S.; Kühnöl, Caspar D.; Föll, Jürgen (Frontiers in Oncology, 2015)
Interleukin-2 (IL-2) transgenic Ewing sarcoma cells can induce tumor specific T and NK cell responses and reduce tumor growth in vivo and in vitro. Nevertheless, the efficiency of this stimulation is not high enough to inhibit tumor growth completely. In addition to recognition of the cognate antigen, optimal T cell stimulation requires signals from so-called co-stimulatory molecules. Several members of the tumor necrosis factor superfamily (TNFSF) have been identified as co-stimulatory molecules that can augment anti-tumor immune responses. OX40 (CD134) and OX40 ligand (OX40L = CD252; also known as tumor necrosis factor ligand family member 4) is one example for such receptor/ligand pair with co-stimulatory function. In the present investigation we generated OX40L transgenic Ewing sarcoma cells and tested their immuno-stimulatory activity in vitro. OX40L transgenic Ewing sarcoma cells showed preserved expression of Ewing sarcoma associated (anti)gens including lipase member I (LIPI), cyclin D1 (CCND1), cytochrome P450 family member 26B1 (CYP26B1) and the Ewing sarcoma breakpoint region 1-friend leukemia virus integration 1 (EWSR1-FLI1) oncogene. OX40L expressing tumor cells showed a trend for enhanced immune stimulation against Ewing sarcoma cells in combination with IL-2 and stimulation of CD137. Our data suggest that inclusion of the OX40/OX40L pathway of co-stimulation might improve immunotherapy strategies for treatment of Ewing sarcoma.